2020
DOI: 10.1016/j.psj.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parachlorophenylalanine treatment on the activity of gonadal and lactotrophic axes in native Polish crested chickens stimulated to broodiness

Abstract: Brooding behavior, a common characteristic of native breeds of the domestic chicken, is marked by elevated prolactin ( PRL ) levels, which is necessary for incubation and connected with changes in hypothalamic–pituitary–gonadal axis activity. Evidence indicates the serotoninergic system is a potent modulator of PRL secretion. The objective of this study is to investigate whether blocking serotonin synthesis with parachlorophenylalanine ( PCPA ) prevents incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…The ELISA method applied in this study has been used for the determination of the levels of plasma gonadal steroid hormones and PRL for several years in the laboratory of the Department of Animal Science of The Hebrew University of Jerusalem in Israel. Until now, it has been used for the evaluation of gonadal steroids in plasma of domestic turkeys [ 31 ] and these hormones and PRL in laying [ 32 ] and broiler breeder chickens [ 33 , 34 ] and domestic geese [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ELISA method applied in this study has been used for the determination of the levels of plasma gonadal steroid hormones and PRL for several years in the laboratory of the Department of Animal Science of The Hebrew University of Jerusalem in Israel. Until now, it has been used for the evaluation of gonadal steroids in plasma of domestic turkeys [ 31 ] and these hormones and PRL in laying [ 32 ] and broiler breeder chickens [ 33 , 34 ] and domestic geese [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that by the end of the breeding–laying period some geese created natural nests. In chickens [ 32 ] and geese [ 35 ], incubation behaviour is related to plasma PRL elevation. Contrary to presented results, in long-day breeding geese Yang et al [ 14 ] observed that PRL level was the highest during the peak of egg production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonadotropins regulate the secretion of gonadotropic hormones through blood circulation, which in turn promotes gonadal development and regulates animal reproduction ( Zhu et al, 2019a ; Zhu et al, 2019b ). In addition, in seasonally breeding avian species, nesting behavior associated with reproduction is an important biological feature and is related to neurotransmitters produced by the hypothalamus, pituitary gland and hypothalamus-pituitary-Gonadal axis (HPG)reproductive hormones ( Saelim et al, 2004 ; Gumułka et al, 2020 ). The HPG axis secretes a variety of hormones, including GnRH hormone at the hypothalamic level, prolactin (PRL),follicle-stimulating hormone (FSH), and luteinizing hormone (LH) hormones at the pituitary level, and E2 and P4 at the gonadal level and the nesting behavior is mediated by the action of ovarian E2 on the hypothalamus during egg laying, and that the enhanced activity of hypothalamic dopamine and pentraxin promotes the synthesis and release of Vasoactive Intestinal peptide (VIP) ( Gumułka et al, 2020 ), which in turn promotes the secretion of PRL through feedback ( Avital-Cohen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heredity is also a fundamental factor that modulates broodiness. Emerging reports demonstrate that broodiness is a polygenic trait regulated by at least 2 dominant autosomal genes, implicated in multiple signal transduction pathways, including GnRH and Wnt pathways ( Yu et al, 2016a ; Gumułka et al, 2020 ). Heritability of nesting sex for waterfowl is only 0.116.…”
Section: Introductionmentioning
confidence: 99%